Penanaman Nilai-Nilai Pancasila dalam Pembelajaran Jarak Jauh pada Pendidikan Tinggi Hukum di Indonesia Era Covid-19: Nurturing Pancasila Values in Distance Learning in Legal Higher Education in Indonesia in the Covid-19 Era - Armadhany, Vita Fatimah (Fakultas Hukum Universitas Negeri Semarang, 2021)
Since Corona Virus Disease 19 (COVID-19) was confirmed to have entered Indonesia in March 2020, this global epidemic has continued to spread and claimed lives. The government has imposed social restrictions on the workplace environment, industry, religion, and education in order to prevent the spread of COVID19. Therefore, students from primary education to higher education must conduct learning activities through distance communication. Furthermore, long distance learning is implemented to all majors at the higher education level, including higher education in law. In addition to using technology as an academic infrastructure, the law faculty must respond to changes in society in the industrial revolution 4.0 era, which changes dynamically, despite the fact that political constraints frequently affect the dynamics of law development in Indonesia. What's more, technology-based law education is expected to continue producing virtuous graduates as the successors for law enforcement and justice in Indonesia who uphold Pancasila's values as the nation's ideology. The spirit of the national ideology is the background of the author's research on the deployment of technology as legal education infrastructure in Indonesia during the COVID19 pandemic, the role of technology in adapting to the legal academic subfield, and how to implement the ideology of Pancasila related to the use of technology as a learning infrastructure and a space for lecture materials. This legal study is a socio-legal perspective. The data used are drawn from primary and secondary legal sources, and the findings are presented deductively. During COVID-19, the result shows that students will use technology as a learning tool in the form of WhatsApp, Google Class, Google Meet, and Zoom. In addition, students also use e-libraries and YouTube channels to enrich reference materials during the learning process. As for technology as an accommodation of scientific substance, students develop it in research. And Pancasila's values ​​are reflected in the attitude of the distance-taught students, and based on Pancasila's ideology for technical and legal research.